PENGARUH KUALITAS PELAYANAN DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS PELANGGAN PADA PT SUMBER ALFARIA TRIJAYA TBK - Riki Supiyani; Sri Afridola (Jurnal Ilmiah Ekonomi Manajemen: Jurnal Ilmiah Multi Science, 2020)
The development of the retail business, at the same time as a rapid development should no longer be managed traditionally, but in a modern way so that it becomes an innovative, dynamic, and competitive business. One of the advantages in running a retail business is that it has a broad market reach, not only opening retail in big cities, but also extending to the edge of the city. PT Sumber Alfaria Trijaya Tbk is better known as Alfamart which was established in 1989 by Djoko Susanto. Competition in the world of commerce is felt and changes in the environment and technology are increasingly rapid and continue to support competition today, customer-oriented marketing strategies, making retail companies must understand well the behavior and needs of their customers to achieve maximum benefits for Alfamart, Alfamart is a retail provide various daily needs for consumption by the community. Alfamartm provides staple goods at affordable prices, convenient shopping, and locations that are easily accessible. This study aims to identify the effect of service quality and customer satisfaction on customer loyalty to PT Sumber Alfaria Trijaya Tbk. The sampling technique used to collect data in this study was random sampling determined in accordance with the coverage area of each service unit by distributing questionnaires to customers. With a total questionnaire of 382 customers from PT Sumber Alfaria Trijaya Tbk. Data were analyzed using Structural Equation Model (SEM). The results of this study stated that service quality has a positive and significant influence on customer loyalty. Consumer satisfaction has a positive and significant effect on customer loyalty.Keywords: Service Quality; Consumer Satisfaction; Loyalty Customer